Revolutionizing healthcare with an in-depth analysis of AI's transformative impact in India - S. Gnana Sanga Mithra; S. Bhavana (Social Sciences and Humanities Open)
This research explores the transformative role of Artificial Intelligence (AI) in India's healthcare sector through an in-depth secondary analysis of existing literature. Focusing on key areas such as diagnostics, patient engagement, and healthcare delivery, the study highlights the significant impact of AI technologies, especially in rural and underserved regions. The analysis underscores AI's potential to bridge healthcare disparities by enhancing accessibility and efficiency, with applications ranging from telemedicine to AI-driven diagnostic tools. Additionally, the study addresses the challenges associated with AI integration, including ethical considerations, policy frameworks, and the need for collaborative efforts to maximize AI's benefits while safeguarding patient welfare. This research provides valuable insights for healthcare professionals, policymakers, and AI developers, offering strategic guidance for the effective integration of AI technologies into India's healthcare system.